PENINGKATAN TEKNIK PASSING BAWAH BOLAVOLI MELALUI PEMANFAATAN MEDIA PEMBELAJARAN PROJECTED MOTION MEDIA PADA SISWA SMK KESEHATAN MEGA REZKY MAKASSAR - Awaluddin, Awaluddin; Nurhidayatullah, Nurhidayatullah (Jurnal Penjaskesrek, 2018)
This research aimed to increase the underhand passing technique of Volleyball through the use of projected motion media for the students of class XI at SMK Kesehatan Mega Rezky Makassar. This research was classroom action research. The sucjects of this research consisted of 23 students. The data analysis technique used descriptive analysis. Based on the results of recapitulation between cycles after applying implementation of Projected Motion Media in cycle two showed that under-passing technique in volleyball game for the students of class XI at SMK Kesehatan Mega Rezky Makassar had increased. The result of cycle 1 was 2 students (8,68%) on scale 4 (good), 8 students (34,78%) on scale 3 (fair) and 10 students (43,47%) scale 2 (poor), and 3 students (13,04%) scale 1 (very poor), while in cycle II there were 4 students (30,77%) on scale 4 (good), and 9 students (69,23%) on scale 3 (fair) and there was not student on scale 2 (poor or very poor). The result of research can be concluded that there is improvement of the underhand passing technique of volleyball through the use of projected motion media for the students of class XI at SMK Kesehatan Mega Rezky Makassar in cycle I dan cycle II